Self-Accountability and its Relationship with ‎Job Performance Level among Departments‏’‏‎ ‎Heads of Directorates of Education in Jordan - Al-Kanji ‎, Rawan; Al-Qudah, ‏"‏Mohammad Amin‏"‏‎ (Jordan Journal of Educational Sciences, 2024)
The present study aimed to investigate the self-accountability level and its relationship with job performance among departments’ heads of directorates of education in Jordan. The study adopted a descriptive-correlative survey-based approach. Data was collected through a survey that included 59 items and was passed to 180 heads of departments working during the academic year (2021- 2022). The survey revealed a high extent of practicing the areas of self-accountability and job performance level.. Results related to relationship examination indicated that there is a statistically significant direct relationship at (α = 0.05) between self-accountability and job performance as a whole, and there is no statistically significant direct relationship at (α = 0.05) between self-confidence and human relationships. The researchers of the present study recommend continuing to adopt training programs directed at educational leaders and workers. These programs clarify the concept of self-accountability, how to apply it within standards, and its impact on the quality of outputs